Effect of Early Essential Newborn Care on Reducing the Neonatal Morbidity and Mortality - Fatima, Ghulam; Shaikh, Shahida; Munir, Badar (Biological and Clinical Sciences Research Journal, 2025)
Neonatal morbidity and mortality remain critical public health challenges, particularly in low- and middle-income countries. Objective: To assess the impact of EENC on neonatal hypothermia, early-onset sepsis, NICU admissions, breastfeeding initiation, and mortality in a tertiary care setting. Methods: This prospective observational study was conducted at Sheikh Zayed Hospital, Rahim Yar Khan. A total of 85 neonates were enrolled in the study. The sample size was determined based on previous research suggesting a significant reduction in neonatal complications with EENC implementation. Results: The post-EENC group showed a significant reduction in hypothermia (7.1% vs. 24.7%, p=0.01) and early-onset sepsis (8.2% vs. 18.8%, p=0.04) compared to the pre-EENC group. NICU admissions decreased (10.5% vs. 22.3%, p=0.03), and timely breastfeeding initiation improved markedly (92.9% vs. 58.8%, p=0.001). Although neonatal mortality was lower in the EENC group (1.2% vs. 7.1%), this difference was not statistically significant (p=0.09). No adverse outcomes associated with EENC were reported. Conclusion: EENC is a safe and effective strategy that significantly improves early neonatal outcomes. Its implementation is associated with reduced hypothermia, infections, and NICU admissions, as well as enhanced early breastfeeding. These findings support the routine adoption of EENC protocols in clinical practice to reduce preventable neonatal morbidity and mortality.